Early Poverty and Future Life Expectancy with Disability among the Elderly in Argentina - Malena Monteverde (Revista Latinoamericana de Población, 2019)
Two aspects of the aging process in Latin America should be specially taken into account in order to evaluate future perspectives of morbidity among the elderly in the region: 1) Cohorts who will compose the bulk of the elderly population in the 21st century in Latin America survived to old age largely because of improvements in medicine and to a much lesser extent to amelioration of living standards, as it is the case in high income countries, and 2) a high proportion of the Latin American population still live in poor economic conditions and even these vulnerable individuals continue to experience gains in (adult and older adult) survival. We aim to evaluate to what an extent recent levels of poverty and indigence among young children in Argentina could impact future levels of disability and demands for long-term care of older people. Our results show that given the levels of poverty and indigence in childhood observed between 1988 and 1994, the relationship between poor early conditions, and the risk of being disabled among the elderly in Argentina, life expectancy with disability at age 60 years old would increase substantially between 2000 and 2040, both in absolute and relative terms.